Psychometric properties of the Spanish version of the barriers to being active quiz among university students in Colombia (2015)
Objective: The Barriers to Being Active Quiz (BBAQ) measures seven barriers to being physically active. The test was translated into Spanish by the team that developed its original English version, but it lacks of the validity assessment studies. The aim of this study was to evaluate the psychometric properties of BBAQ (21 items version), focusing on the reliability and validity. Material and methods: A total of 2634 (1462 female and 1172 male; age 18-30 years) university students completed the BBAQ-21 items questionnaire. Cronbach alpha was calculated to assess the internal consistency. Intraclass correlation coefficients (ICC) and degree of agreement were calculated to assess the test-retest reliability, with a period of 7 days between both administrations, as a measure of reproducibility. An exploratory factor analysis (EFA) and confirmatory (CFA) were done to analyze the validity of BBAQ-21 items. Results: The Cronbach alpha coefficient of BBAQ-21 showed between 0,812 and 0,844 and ICC ranged between 0,46 and 0,87. The degree of agreement for all individual items ranged from 45% to 80%. The EFA showed a 4-factor solution that explained 52,90% of the variance and CFA showed moderate factor loadings. Conclusion: Results support the use of this questionnaire with populations of university students, considering its reliability and validity. BBAQ-21 is available to assess the barriers to physical activity in Latin America. © 2015, Grupo Aula Medica S.A. All rights reserved.